Experimental Investigation of GFRP-Reinforced Hollow Square Concrete Column (Journal of Engineering, 2024)
Due to their great structural efficiency and efficient utilization of materials, steel-reinforced hollow-core concrete columns are often employed in utility poles, ground piles, and piers for bridges. Based on research, these columns' performance is impacted by many design parameters. However, corrosion can be a problem in steel-reinforced concrete structures. This paper examines the differences between using steel and GFRP longitudinal bars in hollow-section square concrete columns and explores the potential benefits of using GFRP bars as an option that is economically viable and non-corrosive. According to the study results, the computational results clearly show how an increased longitudinal GFRP reinforcement ratio improves the columns' bearing capability, but when compared to steel reinforcement, it provides less bearing capability. For the same reinforcement ratio (1.46 %, 3.29 %, and 4.9 %), The findings demonstrated that GFRP columns had a decrease in the axial bearing load by 13.1%, 9.2 %, and 9.4%, respectively.